Desain Sistem On-Grid Energi Terbarukan Skala Rumah Tangga Menggunakan Perangkat Lunak HOMER - Bandiyah Sri Aprillia; Desri Kristina Silalahi; Muhammad Agung Foury Rigoursyah (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
Bandung is located on the island of Java with Latitude -7.5 and longitude 107.5. This location has average solar radiation of 4.89 KWh / m2per day so suitable for solar energy utilization. Solar energy can be converted into electrical energy through photovoltaic system so that it can be applied to residential load. The design of solar power plants for residential load requires accurate calculations. In this research, HOMER was used to evaluate the design of renewable energy on grid systems at residential load 900 VA in Bandung. The research method used arecollecting solar radiation data, equipment specifications and 900 VA electrical load studies. Based on the results of the design on grid photovoltaic system using HOMER, the configuration of 6 PV 2040 Wp units, 4 unit batteries, and 2 kW inverter is the optimum configuration. The system configuration can provide 45.5% of the total daily loadconsumption with the lowest total Net Present Cost (NPC) is IDR 75,300,000.00. The On Grid system that has been designed will achieve an annual profit IDR 1,806,884.00 compared to conventional electricity usage (PLN) and only takes 7 years to recover investment costs.